OPTIMALISASI PRODUKSI KERIPIK TALAS DAN KERIPIK PISANG DI DUKUH CEKEL JETIS SAPTOSARI GUNUNG KIDUL - Totok Suwanda; Krisdiyanto Krisdiyanto; Nur Ardiyansyah; Fitroh Anugrah Kusuma Yudha (Nindikayla Institute, 2023)
The Community Partnership Program has a targeted community of Cekel artisans of taro chips and banana chips. The partners involved are banana chip business actors (Cakrawala All-Business Cooperative) and taro chips business (Zahra) in Cekel, Jetis Saptosari Gunung Kidul. The problems found in partners are slicing fried foods for too long and not optimal, banana mixes are not safe, knowledge of product variations is limited. The solution that can be done is product management counseling that will ensure the quality of handling banana chips and taro chips products. The provision of production equipment assistance will facilitate and speed up work so as to increase productivity. Taro stripping using a double blade, plowing using a chopper machine, slicing using a spinner. Production increased, sales increased. Increased production and sales will improve well-being. Increased insight and additional knowledge of diversification of processed banana, cassava, and peanut products. There is a transfer of technological innovations so as to increase the pace of production, product quality and work safety. There is an increase in the production rate occurring in the slicing process which originally took 30 minutes to 2 to 3 minutes. The improvement of product quality occurs by draining the oil of natural slicing residue using a spinner. Work safety is improved by avoiding oil splashes on the hands during banana plowing